2021
DOI: 10.1039/d1nr01279g
|View full text |Cite
|
Sign up to set email alerts
|

Air-stable and efficient electron doping of monolayer MoS2 by salt–crown ether treatment

Abstract: To maximize the potential of transition-metal dichalcogenides (TMDCs) in device applications, the development of a sophisticated technique for stable and highly efficient carrier doping is critical. Here, we report the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…Multilayer Nb x Mo 1– x S 2 and WSe 2 flakes were prepared by mechanical exfoliation of bulk crystals on SiO 2 (285 nm)/Si substrates. MoS 2 was grown via salt-assisted CVD using a lab-made setup with two electric furnaces. ,, The exfoliated Nb x Mo 1– x S 2 or WSe 2 flakes on SiO 2 /Si substrates were placed in a quartz tube, and MoO 2 powder (40–70 mg), KBr powder (3–8 mg), and sulfur flakes (2–3 g) were placed 1, 2, and 30 cm upstream from the substrates, respectively. The quartz tube was then filled with N 2 gas at flow rates of 150–300 sccm.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Multilayer Nb x Mo 1– x S 2 and WSe 2 flakes were prepared by mechanical exfoliation of bulk crystals on SiO 2 (285 nm)/Si substrates. MoS 2 was grown via salt-assisted CVD using a lab-made setup with two electric furnaces. ,, The exfoliated Nb x Mo 1– x S 2 or WSe 2 flakes on SiO 2 /Si substrates were placed in a quartz tube, and MoO 2 powder (40–70 mg), KBr powder (3–8 mg), and sulfur flakes (2–3 g) were placed 1, 2, and 30 cm upstream from the substrates, respectively. The quartz tube was then filled with N 2 gas at flow rates of 150–300 sccm.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…We would like to show a representative approach to the stable doping of MoS 2 monolayer and its full characterization. Miyata and colleagues have recently reported that MoS 2 monolayer doped with the compexes of potassium hydroxide and crown ether shows air-stable, metallic conduction [48]. They found a dramatic increase in current density in MoS 2 field effect transistors upon the supramolecular doping.…”
Section: Molecularly and Supramolecularly Doped N-type Transition-met...mentioning
confidence: 99%
“…Surface charge transfer doping has been employed to tune a wide range of carrier concentrations in TMDCs on metal-oxide-semiconductor FETs (MOSFETs). This doping method causes no damage to the lattice, and the doping level is available to a degenerate state at 10 13 cm –2 in both n- and p-types in TMDCs. One of the strongest modulating agents is an organic dopant, the benzyl viologen (BV) molecule, because it has a high reduction potential. , Previously, BV molecules have achieved electron doping into MoS 2 MOSFETs over the 10 13 cm –2 range in a multilayer flake . The postdoped MOSFETs showed a small gate voltage ( V G ) dependence, indicating a degenerately doped state in the channel MoS 2 . ,, This level of high carrier concentrations would further induce metallic or quantum phase transformations.…”
Section: Introductionmentioning
confidence: 99%